The Changes of Cultural Memory in a Liquid Modern World - Mykolaitytė, Aurelija (Respectus Philologicus, 2020)
Based on the insights of modern philosophers, particularly Zygmunt Bauman, the work examines how cultural memory can be affected by globalisation and what kind of challenges arise when collective truths are passed on from generation to generation. The sources selected for the analysis are modern dystopias that design possible versions of cultural response. Other subjects significant to the research include phenomena of modern culture that help to uncover the latest trends and the views on cultural heritage held by people of the 21st century. The article comes to the conclusion that the changes of cultural memory in a fluid modern world can be affected deeply by factors such as the ideology of consumerism and the insularity of a web community, but this is only a possibility. Western authors Aldous Huxley and Michel Houellebecq place a stronger emphasis on determinism, whereas Lithuanian writer Jaroslavas Melnikas highlights the possibility of freedom. Nevertheless, notably, all of these texts are projections that primarily encourage critical thinking and demonstrate the ambivalence of the current situation. Contemporary culture is likely at a turning point, but the results of the transformation are still unclear.
Keywords: cultural memory; globalisation; web community; dystopia; contemporary art